Through the fog : towards inclusive anti-racist teaching - Affolter, Tara L. (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
Drawing from over 20 years of teaching experience in the U.S., ranging from pre-kindergarten to post-graduate, Affolter illustrates personal, practical, and theoretical ways for teachers to grapple with the complexities of race and racism within their own schools and communities and develop as inclusive anti-racist teachers. The work aims to take into account the deeply human dimensions of inclusive anti- racist teaching, while drawing attention to the threat of burnout, inviting closer inspection of curricula development, and exploring tangible ways to sustain this important work for teaching.Resisting racism, agitating for change, and walking an inclusive anti-racist path requires commitment to unflinchingly look at one's failures and examine silences. It is work that must be done in all settings: rural, urban, suburban. This book offers all pre-teachers and in-service teachers some perspectives and reflections on engaging anti-racist inclusive practice. The questions raised here ask each of us to consider our own positioning and interrogate the stories we tell ourselves about "the other." The book seeks to call in white teachers in particular to carefully examine our own biases and the ways we may replicate white supremacist ideology within our pedagogy and curricula. The questions posed here and the work ahead is not easy. This is work best taken on with those that can challenge with love and help support one other as we imagine and work towards a more just world.
Keywords: Racism in education -- United States.; Discrimination in education -- United States.; Educational equalization -- United States.; Minorities -- Education -- United States.; Teachers -- United States -- Attitudes.; Education -- Teaching -- Methods & Strategies.; Teaching skills and techniques.; elektronické knihy; electronic books